Assessment of Waste Management System Among Hotels and Guest Houses in Minna - OLUWOLE, Ebenezer Adegboyega; ATTAHIRU, Hamza; OYEDIRAN, Olorunfemi Boye; OMOTUGBA, Stephen Kayode; MEDUNA, Patience Ndidi; KOLAWOLE, Gbemiga Thaddaeus (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020DO - 10.14505//jemt.v11.7(47).02, 2020)
The production and management of waste has become an important point of interest for hoteliers and their managers globally due to its environmental impacts. In the bid to become more sustainable or environmentally responsible, hotels and guest houses are going green. Thus, this study examines waste management system adopted lodging facilities in Minna, Niger State. Data collection was performed using questionnaire administered to managers of 26 sampled lodging facilities. Result revealed that three units (rooms, kitchen and store/wharehouse) out of the nine units examined produce the highest volume of wastes As plastic, paper, organic, and water wastes are topmost in the categories of wastes produce, while large percentage of the wastes are either burnt, landfill, or dump in the water ways or municipal dump site without seperation. The findings will help foster a new paradigm shift to mitigate the environmental impact of the waste produced by accomoodation outfits.